Walking the Tightrope: A Proposed Model of Chronic Pain and Stress - Lunde, Claire E.; Sieberg, Christine B. (Frontiers in Neuroscience, 2020)
Pain and stress are both phenomena that challenge an individual's homeostasis and have significant overlap in conceptual and physiological processes. Allostasis is the ability to adapt to pain and stress and maintain homeostasis; however, if either process becomes chronic, it may lead to long-term maladaptive changes in physiology and behavior. The negative effects of stress on health outcomes, including pain, have been well documented; however, the specific mechanisms of how stress and what quantity of stress contributes to the maintenance and exacerbation of pain have not been identified, and thus pharmacological interventions are lacking. The objective of this brief review is to: 1. Identify the gaps in the literature on the impact of acute and chronic stress on chronic pain, 2. Highlight future directions for stress and chronic pain research; and 3. Introduce the Pain- Stress Model in the context of the current literature on stress and chronic pain. A better understanding of the connection between stress and chronic pain could provide greater insight into the neurobiology of these processes and contribute to individualized treatment for pain rehabilitation and drug development for these often comorbid conditions.